Relative Serum Antiplasmin Levels in Normal and Hemophilic Dogs Treated with Choline - McDonald, D; Jackson, Blanche; Boudreaux, H. B; Myers, R. B (Thrombosis and Haemostasis, 1972)
Peroral administration of choline in relatively high dosage (300 or 600 mg choline dihydrogen citrate per 17-20 lb body weight, 4 times daily) caused no significant change in serum antiplasmin activity of either normal or factor VIII-deficient beagle dogs. Also, no alteration in antiplasmin level was found to be associated with the hemophilic state.Canine serum antiplasmins are stable at low temperatures. Like human antiplasmins, they appear to have two major components which differ conspicuously in stability at 60° C.Other data presented in this paper show that crude plasmin readily obtained from human serum euglobulins provides an enzyme preparation suitable for screening antiplasmin levels of sera by the caseinolytic method.